Synthesis of Novel Benzothiazole–Profen Hybrid Amides as Potential NSAID Candidates - Iliyan Ivanov; Stanimir Manolov; Dimitar Bojilov; Yordan Stremski; Gabriel Marc; Stela Statkova-Abeghe; Smaranda Oniga; Ovidiu Oniga; Paraskev Nedialkov (Molecules)
Herein, we report the synthesis of a series of new compounds by combining 2-aminobenzothiazole with various profens. The compounds were characterized using techniques such as 1H- and 13C-NMR, FT-IR spectrometry, and high-resolution mass spectrometry (HRMS), with detailed HRMS analysis conducted for each molecule. Their biological activities were tested in vitro, revealing significant anti-inflammatory and antioxidant effects, comparable to those of standard reference compounds. Lipophilicity was experimentally determined through partition coefficient (RM) measurements. To understand their binding affinity, molecular docking studies were perfsormed to analyze interactions with human serum albumin (HSA). The stability of these predicted complexes was further evaluated through molecular dynamics simulations. The results highlight the compounds’ promising biological activity and strong affinity for HSA. The new hybrid molecule between 2-ABT and ketoprofen 3b demonstrates significant promise based on the experimental data and is further supported by in silico calculations. Compound 3b exhibits the best hydrogen peroxide scavenging activity among the tested compounds, with an IC50 of 60.24 μg/mL. Furthermore, 3b also displays superior anti-inflammatory activity, with an IC50 of 54.64 μg/mL, making it more effective than the standard ibuprofen (76.05 μg/mL).